Customisation versus Personalisation of Digital Health Information - Minh Hao Nguyen; Nadine Bol; Andy J. King (University of Zurich, IKMZ - Department of Communication and Media Research, 2020)
Health information is increasingly conveyed to patients in digital formats, such as through health websites, patient portals, and electronic health records. However, for people to be able to process information effectively, information must be presented in a suitable format. This study examines the effectiveness of different strategies for tailoring the mode of presentation (i.e., using textual, visual, and/or audio-visual formats) on information processing outcomes among different audiences (i.e., lower vs. higher health literates; younger [25-45 years] vs. older adults [?65 years]). In an online experiment participants viewed either a customized, personalized, or non-tailored (mismatched) website based on individual preferences for presentation mode. We analysed a 3 (condition) × 2 (health literacy level) × 2 (age group) between-subjects design, examining effects on: time spent online, attention, perceived relevance, website involvement, website satisfaction, and information recall. Results (N = 490) showed that mode tailoring, by both customization and personalisation, is more effective than no tailoring. However, contingent on the outcome variable (i.e., attention, website satisfaction, information recall), or health literacy level, and age group, different tailoring strategies show different effects. Designers of digital health information should strategically consider employing personalized information modes or to have people to customize their own information materials.